1974
DOI: 10.1152/ajplegacy.1974.227.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of end-plate desensitization by sodium

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1976
1976
1984
1984

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This linearity has been reported by Harrington (1973) for the membrane voltage response, measured directly with microelectrodes, to agonist applied by microperfusion. It is difficult to determine the exact nature of the interaction between ACh and the receptor from this type of plot because of desensitization of the response (e.g., Parsons, Schnitzler, and Cochrane, 1974), possible shifts in intracellular C1-concentration (Jenkinson and Terrar, 1973), and the voltage dependency of the ACh-activated membrane conductance (Dionne and Stevens, 1975). The double reciprocal plot is, however, useful for estimating the maximum ACh-activated voltage response, AV,,,, from the reciprocal of the Y-axis intercept.…”
Section: Methodsmentioning
confidence: 99%
“…This linearity has been reported by Harrington (1973) for the membrane voltage response, measured directly with microelectrodes, to agonist applied by microperfusion. It is difficult to determine the exact nature of the interaction between ACh and the receptor from this type of plot because of desensitization of the response (e.g., Parsons, Schnitzler, and Cochrane, 1974), possible shifts in intracellular C1-concentration (Jenkinson and Terrar, 1973), and the voltage dependency of the ACh-activated membrane conductance (Dionne and Stevens, 1975). The double reciprocal plot is, however, useful for estimating the maximum ACh-activated voltage response, AV,,,, from the reciprocal of the Y-axis intercept.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, X-537A rapidly depolarizes muscle fibres maintained in normal sodium Ringer solution presumably because this agent transports monovalent as well as divalent cations (Pressman, 1973;Devore & Nastuk, 1975;Schnitzler & Parsons, unpublished observations). As desensitization rate is influenced both by membrane potential (Magazanik & Vyskocil, 1970) and by intracellular sodium (Manthey, 1966;Parsons et al, 1974) (Manthey, 1966;Johnson & Parsons, 1972). The junctional region of individual muscle fibres was (Nastuk & Parsons, 1970;Manthey, 1972).…”
Section: General Methodsmentioning
confidence: 99%
“…In the continued presence of recently that this site is located on the internal surface agonist, the conductance gradually returns toward the of the postjunctional membrane and therefore is pre-activation state as 'desensitization' occurs distinct from the agonist-recognition site on the (Thesleff, 1955). Manthey (1966) has shown that external surface of this membrane (Nastuk & Parsons, raising the external calcium concentration accelerates 1970; Cochrane & Parsons, 1972;Parsons, Schnitzler & Cochrane, 1974). This view would be greatly…”
Section: Introductionmentioning
confidence: 98%
“…In spite of the fact that our understanding of the molecular aspects of receptor-channel gating at the motor end-plate has increased markedly in recent years, the molecular mechanism responsible for the development of desensitization still remains obscure. There are a number of environmental factors such as membrane voltage, extracellular and intracellular ionic concentrations, and agonist concentration which can markedly alter the time course of onset of desensitization (Manthey, 1966;Magazanik & Vyskocil, 1970;Nastuk & Parsons, 1970;Parsons, Schnitzler & Cochrane, 1974; De Bassio, Parsons & Schnitzler, 1976;Parsons, 1978;Chestnut, 1983). The development of desensitization is particularly sensitive to the extent of receptor-channel activation.…”
Section: Introductionmentioning
confidence: 99%